Between Reality and Virtuality: A Study of Muslim Perceptions of Metaverse Hajj as a Religious Practice - Hasse Jubba; Henky Fernando; Yuniar Galuh Larasati; Muhammad Rifai Darus (Khazanah Theologia, 2024)
Purpose: This study explores Muslim perceptions and evaluations of virtual Hajj within the metaverse, focusing on its acceptance as a religious practice. Methodology: Utilising a qualitative descriptive approach, data were sourced from online news articles identified using the search term "Metaverse Hajj Discourse" on Google. These articles were analyzed to understand the diverse perspectives within the Muslim community regarding virtual Hajj. Findings: The research reveals that while Muslims acknowledge the educational and preparatory benefits of virtual Hajj, it is largely rejected as a legitimate form of fulfilling the religious obligations of Hajj, due to its failure to encapsulate the physical and spiritual elements of the pilgrimage. Research Implications: This study highlights the need for a nuanced understanding of virtual religious practices, suggesting that while such technologies can augment the educational aspects of religious rituals, they cannot replace the physical acts prescribed by religious doctrines. Originality/Value: The research contributes to the emerging discourse on religious practices within digital spaces, offering insights into the intersection of technology and traditional religious practices, and setting a foundation for future theological discussions on virtual reality's role in religion.